2001
DOI: 10.1093/ije/30.2.326
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health. Comparisons between three different measures. Results from a population study

Abstract: The results imply that non-comparative measures are more appropriate in longitudinal studies and that measures without specified response options might be less suitable for an older study group. The overall impression is, however, that the different measures represents parallel assessments of subjective health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
329
2
23

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(373 citation statements)
references
References 14 publications
19
329
2
23
Order By: Relevance
“…To our knowledge, this is the first study to show that the two most commonly used versions of subjective global health are not directly comparable within and across countries, but relate similarly to other covariates. Consistent with findings from single populations [12], we found that different measures of self-rated health are strongly correlated. Our results confirm findings from previous research suggesting that different measures of self-rated health represent parallel assessments of subjective health [12].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To our knowledge, this is the first study to show that the two most commonly used versions of subjective global health are not directly comparable within and across countries, but relate similarly to other covariates. Consistent with findings from single populations [12], we found that different measures of self-rated health are strongly correlated. Our results confirm findings from previous research suggesting that different measures of self-rated health represent parallel assessments of subjective health [12].…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with findings from single populations [12], we found that different measures of self-rated health are strongly correlated. Our results confirm findings from previous research suggesting that different measures of self-rated health represent parallel assessments of subjective health [12]. Differences between countries in the level of self-rated health and the association of this variable with socioeconomic and health factors have been reported [10,11,[26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…La auto percepción del estado de salud se ha convertido en una herramienta predictiva muy poderosa del futuro estado de morbilidad y mortalidad en la población, aún controlando una variedad de características físicas, sociodemográficas y psicosociales (5). Este indicador puede reflejar enfermedades que no son detectables en forma bio médica o que no están incluidas en un examen médico.…”
Section: Introductionunclassified
“…Moreover, dietary habits that children and youth established in childhood were often associated with the same habits they maintain in adulthood [10]. In relation with nutrition, findings showed that SES had strong impact on physical activity in adolescents [11,12]. One study reported, that maternal education level positively influenced on self-reported physical activity in adolescents [13].…”
Section: Introductionmentioning
confidence: 99%